Relative efforts of countries to conserve world’s megafauna - Lindsey, P; Chapron, G; Petracca, L; Burnham, D; Hayward, M; Henschel, P; Hinks, A; Garnett, S; Macdonald, D; Macdonald, E; Ripple, W; Zander, K; et al. (Elsevier, 2017)
Surprisingly little attention has been paid to variation among countries in contributions to conservation. As a first step, we developed a Megafauna Conservation Index (MCI) that assesses the spatial, ecological and financial contributions of 152 nations towards conservation of the world’s terrestrial megafauna. We chose megafauna because they are particularly valuable in economic, ecological and societal terms, and are challenging and expensive to conserve. We categorised these 152 countries as being above- or below-average performers based on whether their contribution to megafauna conservation was higher or lower than the global mean; ‘major’ performers or underperformers were those whose contribution exceeded 1 SD over or under the mean, respectively. Ninety percent of countries in North/Central America and 70% of countries in Africa were classified as major or above-average performers, while approximately one-quarter of countries in Asia (25%) and Europe (21%) were identified as major underperformers. We present our index to emphasize the need for measuring conservation performance, to help nations identify how best they could improve their efforts, and to present a starting point for the development of more robust and inclusive measures (noting how the IUCN Red List evolved over time). Our analysis points to three approaches that countries could adopt to improve their contribution to global megafauna conservation, depending on their circumstances: 1) upgrading or expanding their domestic protected area networks, with a particular emphasis on conserving large carnivore and herbivore habitat, 2) increase funding for conservation at home or abroad, or 3) ‘rewilding’ their landscapes. Once revised and perfected, we recommend publishing regular conservation rankings in the popular media to recognise major-performers, foster healthy pride and competition among nations, and identify ways for governments to improve their performance.